PENGARUH TAHAP DAUR HIDUP PERUSAHAAN, KEBIJAKAN DEVIDEN, DAN KEBIJAKAN HUTANG TERHADAP WEALTH ADDED INDEX - Febriany, Novita; Kusmawati, Kusmawati (Balance : Jurnal Akuntansi dan Bisnis, 2022)
One of the company's goals is to measure the company's performance. The separation of ownership from management in the company creates agency problems. Managers who run companies and usually do not own shareholdings should not act in the best interests of shareholders because they are maximizing their own wealth. This study is to test whether there is an effect of agency costs (spread of ownership and managerial ownership), stages of the company's life cycle, and dividend policy on the wealth added index. The population in this study are companies listed on the SWA100 index. The observation sample was selected using purposive sampling method. The analysis technique used is multiple regression analysis, the significance level used is 5%. The steps taken in this study went through several stages, namely: identifying problems, planning actions, and implementing actions.